Potential of beef tallow/palm oil blend as Chongqing hotpot oil from a physicochemical and flavor perspective - Cen Zhang; Wenjing Lu; Di Chen; Yuhao Zhang; Jie Li; Zhongjun Gou; Chaogeng Xiao (Food Chemistry: X)
Beef tallow is an important raw material in Chongqing hotpot seasoning but raises great concern on health due to the cholesterol issue. Herein, palm oil was expected to replace beef tallow at weight ratios of 2:1, 1:1, and 1:2 without reducing hotpot flavor. The blending of palm oil to beef tallow effectively decreased cholesterol content to 33.20 mg 100 g−1, as well as the level of saturated fatty acids to 50 % in hotpot oil. The fading in brightness and yellowness of oil models occurred owing to heat treatment. The blending oil at 2:1 showed similar hardness, melting and crystallization behaviors to beef tallow, probably due to the similar fat crystal network. The volatile compounds of hotpot seasoning made from the oil were closer to that from neat beef tallow. These findings may provide a new strategy to develop healthier and tastier base oil for the production of Chongqing hotpot seasoning.